Foliar biomass production and litterfall pattern of five timber species in forest plantations of semi-arid lands of the northeastern Mexico - Ngangyo Heya, Maginot; Foroughbakhch Pournavab, Rahim; Carrillo Parra, Artemio; Salas Cruz, Lidia Rosaura; Alvarado Vázquez, Marco Antonio; Bustamante García, Verónica (Sociedad Botánica de México, 2017)
Abstract Background: Fodder shrubs and trees have both economic as well as ecological values in most extensive systems of arid and semiarid regions. Hypothesis: The litterfall represents an important way in maintaining the productivity of these ecosystems, and we hypothesized that its production pattern is related to the foliar biomass production, associated with seasons and species. Studied species: Acacia berlandieri, Acacia wrightii, Ebenopsis ebano, Havardia pallens and Helietta parvifolia. Study site and years of study: The foliar biomass was evaluated seasonally, from the dry weight of a representative branch of each species. The litterfall was collected every 15 days through litter traps installed under tree canopies, in experimental plantations of 30 years old, in the semi-arid zone of northeastern Mexico. Results: The foliar biomass values showed highly significant differences (P < 0.01) among species as well as seasons, whereas leaf litter values presented highly significant differences (P < 0.01) among seasons but not (P > 0.05) among species. The maximum foliar biomass production was registered in summer by E. ebano (9,029 kg ha-1), while the lowest value (103 kg ha-1) was recorded in winter by A. wrightii. The greatest leaf litter accumulation was observed in winter (296 kg ha-1) by A. wrightii, and the lower value was recorded in spring, by E. ebano (97 kg ha-1). A significant linear correlation (R2 = 68,79 %) was determined between accumulation of leaf litter and foliar biomass production in autumn. Concluisions: As conclusion, the leaf litter pattern can be related to the foliar biomass production, depending on the seasons and species. That constitutes a practical tool for the management of the forest ecosystems in semiarid areas. Key words: Foliar biomass, litterfall, timber species, semi-arid zone